Properties of nanofluid as radiator coolant by using MgO nanoparticles / Azmi Roslan ...[et al.] - Roslan, Azmi; Suhail, Muhamad Faiz; Nissa, Khairin; Saaudi, Liyana; Alia, Nur Farisa
This paper studies the experimental result relating nanofluid as coolant. In this experiment, the base fluid used is ethylene glycol and the nanoparticle is magnesium oxide (MgO). This experiment was conducted to identify the effect metal nanoparticle; magnesium oxide in ethylene glycol and ultrapure water. The aim of the experiment is to study the properties of magnesium oxide as nanoparticle in ethylene glycol+Ultrapure water with different concentration. Other than that, this experiment is to identify the effectiveness of this nanofluid as a coolant to apply in automotive and industrial sector. The properties that has been analyzed were specific heat capacity, freezing point and thermal conductivity of magnesium oxide in the ethylene glycol and UPW. For the sample preparation, ethylene glycol was well mixed with ultra-pure water and magnesium oxide powder. As for the specific heat capacity and freezing point properties identification, the experiment were conducted using Differential Scanning Calorimetry, PerkinElmer DSC6000. However, the thermal conductivity experiment were carried out using KD2 Pro Thermal Properties Instrument. The experimental result for thermal conductivity experiment shows that the nanofluid with 0.004vol% of magnesium oxide has the best percentage of improvement with respect to conventional coolant and reference fluid EG-UPW which are 139.94% and 39.29% respectively. The study on the freezing point shows the maximum improvement percentage of 0.004 vol% MgO which is 110.29% while for the specific heat capacity the percentage of improvement is 113.774% respect to reference fluid and 199.745% with respect to conventional coolant.